Relationships between the strengths of character: forgiveness, gratitude, and hope and satisfaction with life among public health and physiotherapy students - Wnuk, Marcin; Marcinkowski, Jerzy T.; Kalisz, Zdzisława (Polish Journal of Public Health, 2010)
Aim. The main aim of this study was to examine whether gratitude is related to forgiveness. An additional aim was to verify if gratitude, forgiveness, and hope are positively correlated with satisfaction in life.Material and methods. The sample consisted of 75 students of public health and physiotherapy graduate courses at the University of Bydgoszcz. The following tools were used: Transgression-Related Interpersonal Motivations Scale - (TRIM-12), Gratitude Questionnaire (Q-6), Herth Hope Index (HHI), Satisfaction with Life Scale (SWLS).Results. A negative relationship between gratitude and motivation to revenge as well as a positive relationship between gratitude and hope were observed. Hope was positively related with life satisfaction.